Efficiency of the Parents’ Behavioral Training Model (Barkley) on the Emotional Regulation of the Children with Attention Deficit Hyperactivity Disorder - nasim javidipour; mareih dehghan (Ravānshināsī-i Afrād-i Istis̠nāyī, 2022)
Attention Deficit Hyperactivity Disorder leads to mental, behavioral, and emotional damage to the infected children. Therefore, the present study was conducted with the aim of investigating the efficacy of parents’ behavioral training model (Barkley) on the emotional regulation of children with attention deficit hyperactivity disorder. The present study was experimental with pretest, posttest, and control group design. The statistical population of the study included male children with attention deficit hyperactivity disorder in the city of Yazd in the autumn and winter of 2018-19. In this study, the sample size was 30 people (15 people in the experimental group and 15 people in the control group) but after the intervention of 2 parents in the experimental group and 2 parents in the control group, they refused to continue the intervention. The parents of the children in the experimental group received eight seventy-five-minute intervention sessions of the parents’ behavioral training model (Barkley) for one month. The applied questionnaires in this study included the attention deficit hyperactivity disorder questionnaire (Brock, Clinton, 2007) and the emotional regulation questionnaire (Shields & Cicchetti, 1997). The data of 26 parents were analyzed by the ANCOVA method using SPSS-23 software. The results showed that the parents’ behavioral training model (Barkley) has a significant effect on the emotional regulation of the children with attention deficit hyperactivity disorder (p<0.001). According to the findings of the present study, it can be concluded that the parents’ behavioral training model (Barkley) can be sued as an efficient method to increase emotional regulation in the children with attention deficit hyperactivity disorder by employing training appropriate methods to decrease the children’s abnormal behavior, the skill of showing positive attention to the children, methods of making positive interaction and managing inappropriate behaviors and the skills of positive attention.